A case of vascularized corneal opacity treated with aflibercept - A.S. Cholak; I.O. Nasinnyk; P.O. Kostenko; S.A. Iakimenko; A.R. Korol (Ukrainian Society of Ophthalmologists, 2020)
Background: Corneal neovascularization (CNV) is a serious condition that can lead to a profound decline in vision. Current research on treating CNV with angiogenesis inhibitors is underway in numerous centers, and a number of studies have demonstrated the efficacy of this approach. Purpose: To present a case of corneal neovascularization treated with aflibercept. Material and Methods: An ocular examination included visual acuity assessment, biomicroscopy, anterior eye photography and fluorescein angiography (FA). In addition, an area of CNV was assessed before and 6 months after a single subconjunctival injection of 4 mg (0.1ml) aflibercept. Results: An area of CNV decreased from 38,081 pixels before injection to 20,782 at 6 months, with a reduction in 17,299 pixels. Conclusion: In the case reported here, a single subconjunctival injection of 4 mg (0.1ml) aflibercept was found to be effective for reducing corneal neovascularization at 6 weeks.